Hazard Factor Identification And Efforts To Control Work Accidents In Welding Activities In Tanks (Confined Space) At PT. Menubar Kaltim - istiarto; Wesi Fatmawati (Universitas Widya Gama Mahakam Samarinda, 2023)
Background: Hazard factors and risks on ships, especially in welding activities in tanks (confined space) there are hazard and risk factors that cannot be avoided by workers. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan pendekatan fenomenologi melalui teknik wawancara, observasi, dan dokumentasi terhadap 6 informan, 3 informan utama dan 2 informan pendukung 1 informan kunci. From the results of research through interviews, it can be known that hazard factors, especially in welding activities in the tank (confined space) there are 17 potential hazards with 19 levels of risk and the impact of each category level including 0 risks being included in the low category, 6 risks of being included in the moderate category, 7 risks being included in the high category, 6 other risks are. There are still workers who do not comply with the importance of work safety, some workers actually know that the hazard factors around them are very risky but workers still carry out unsafe behaviour, forget to use personal protective equipment, do not check first, incomplete equipment and damaged equipment as well as worker awareness in equipment maintenance and maintenance of workplace areas. Objectives : This research aims analayze hazard factor and work accident control efforts in tanks welding activities (confined space) at PT. Menubar Kaltim Research Metodes: The type of research used is qualitative which is a research method carried out with the main aim of giving an objective picture of a situation (Notoatmodjo, 2012). The research design used in this study is by phenomenological approach method. The approach is a study that describes phenomena that occur and can be observed. This study is for (data presentation) and conclucion (verification). Findings: Based on the results of interviews conducted by researchers with main informants, supporting informants, key informants, about hazard factors and efforts to control work accidents in welding activities in tanks (confined space) at PT. MK. The main informants in this study were 3 welding workers in the tank (confined space), 1 safetyman and 1 person in charge of the machine in a limited space as a supporting informant who also conducted supervision in the work area (hot work, confined space) and 1 person as a key informant, namely the supervisor. The main information in this study is that each informant has different knowledge due to the experience of workers while working as regulated according to Law Number 11 concerning Job Creation in 2020 and Undung-Law Number 1 of 1970 concerning work safety. Conclusion: Welding activities in tanks (confined space) have a very high level of work accident risk for welding workers in ship tanks. Welding activities in tanks (confined space) at PT. Menubar Kaltim has all levels of risk categories, namely low, moderate, high to extremely high. The results obtained from data analysis using JSA and RA to determine the results on welding activities in tanks (confined space) 17 potential hazards with 19 risk levels of risk and 0 risk levels of low, 6 moderate, 7 high, 6 extremely high.